Smart rack / Ahmad Imran Yacob ...[et al.] - Yacob, Ahmad Imran; Alias, Muhammad Anas; Mohd Shahrom, Muhammad Khairul Najib; Abd Aziz, Jasmine; Taharudin, Afiqah Izzati; Jalaluddin, Siti Nur Aqilah (2017)
Rack is a fixture containing several tiered shelves and often affixed to a wall which is used in home, business, store or elsewhere to place items that are being stored or displayed. It is raised off the ground and usually supported its shorter length 1 sides by brackets. It also can be held up by columns or pillars. Smart rack is an idea generated by our team to fulfil the needs of daily usage. Referring to the name of product which is 'smart rack', it obviously shows that it rotates differently from any other normal rack. Furthermore, it is programmed to rotate automatically. The concept of this product comes from the idea of carousel storage system and therefore it rotates vertically. The objective of this product is to save space in the kitchen by letting many items store in one place. Also, the dry foods in a storage are orderly kept. With all work hard from the team, we hope this project will be useful for consumer and give the great impact in the current market. The innovation of the rack will make a good satisfaction to all.